A retrospective study of native wild birds and reptiles admitted to three New Zealand wildlife hospitals due to predation by cats. Issue 2 (4th March 2023) - Gartrell, BD; Jolly, M; Tissink, K; Argilla, LS; Esam, F
ABSTRACT: Aims: To investigate the types of wildlife affected and outcomes of hospitalisation for native wild birds and reptiles admitted to three wildlife hospitals in New Zealand following predation by cats. Methods: We reviewed hospital records of three wildlife hospitals (Wildbase Hospital (WBH) in Palmerston North; The Wildlife Hospital – Dunedin (DWH); and The Nest Te Kōhanga (TNTK) in Wellington) for cases of native species with a submission history or diagnosis of predation by cats over the period 2006–2022. Frequency analysis and cross-tabulation of the data were carried out using the factors wildlife hospital, animal order, species, and case outcome. Results: Native wildlife (n = 639) presented following predation by cats to the three wildlife hospitals comprised 598 (93.6%) birds from 31 species and 41 (6.4%) reptiles from eight species. The mortality rate of these patients combined was 61.8% (395/639), with the other 38.2% (244/639) being released from hospital to rehabilitation facilities, released to the wild, or, for a small number, put into permanent captive placements. The most common species of birds admitted due to predation by cats were tūī ( Prosthemadera novaeseelandiae ; n = 173), silvereyes ( Zosterops lateralis ; n = 142), sacred kingfishers ( Todiramphus sanctus ; n = 100) and kererū ( Hemiphaga novaeseelandiae ; n = 70). There was an overall trend to increasing numbers of wildlife admitted for predation by cats over the period of this review, but the different operating periods of the three hospitals should be considered. Each of the three hospitals saw a different mix of species, with Wellington's TNTK seeing the widest diversity of species affected. Conclusions: Predation by cats was a common cause of native birds and reptiles being admitted to all three wildlife hospitals and a diversity of urban and rural wildlife were affected. Clinical relevance: Predation by cats causes significant mortality in wildlife patients admitted to wildlife hospitals despite best current treatment. Cat management strategies in Aotearoa New Zealand should consider the welfare and health of wildlife.